2021
DOI: 10.1029/2020wr027465
|View full text |Cite
|
Sign up to set email alerts
|

Lake Modeling Reveals Management Opportunities for Improving Water Quality Downstream of Transboundary Tropical Dams

Abstract: Sustainable solutions to meet the growing food, water and energy needs of the human population are urgently required, especially in developing countries. Demand for hydropower and irrigation water threatens large river systems with potentially irreparable environmental effects (Best, 2019). More than 3,700 dams are proposed in tropical and subtropical countries (Winemiller et al., 2016;Zarfl et al., 2015). The African continent still has a largely untapped hydropower potential: Only 10% of this potential has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 94 publications
0
18
0
1
Order By: Relevance
“…14 of 52 all pixels within a water body) (MacCallum & Merchant, 2012;Woolway & Merchant, 2017) and within-lake thermal patterns, as well as their responses to climate change (Calamita et al, 2021;Mason et al, 2016;Woolway & Merchant, 2018;Zhong et al, 2016). Specifically, studies that have investigated spatially resolved observations of LSWT demonstrated considerable within-lake warming patterns, with warming rates often differing at sub-basin scales (Kraemer et al, 2015;Mason et al, 2016;Zhong et al, 2016).…”
Section: Satellite Observation Of Lswtmentioning
confidence: 99%
“…14 of 52 all pixels within a water body) (MacCallum & Merchant, 2012;Woolway & Merchant, 2017) and within-lake thermal patterns, as well as their responses to climate change (Calamita et al, 2021;Mason et al, 2016;Woolway & Merchant, 2018;Zhong et al, 2016). Specifically, studies that have investigated spatially resolved observations of LSWT demonstrated considerable within-lake warming patterns, with warming rates often differing at sub-basin scales (Kraemer et al, 2015;Mason et al, 2016;Zhong et al, 2016).…”
Section: Satellite Observation Of Lswtmentioning
confidence: 99%
“…From sampling points further downstream on the Zambezi, we observed a trend of recovery towards near-saturation, though models have suggest that full recovery of dissolved oxygen will only occur aer 380 km at which point the river will have already reached the Cahora Bassa reservoir in Mozambique. 30 The severe hypoxia in the Kafue River below the Itezhi-Tezhi appears to be a new phenomenon driven by a recent change in dam operation. Previously, the Itezhi-Tezhi had served as a supply reservoir for downstream generation at the Kafue Gorge (located at the far end of the Kafue Flats) and discharged lake surface waters through spill gates.…”
Section: Dams and Hypoxiamentioning
confidence: 99%
“…Climate warming could also change strati-cation dynamics by disrupting seasonal re-mixing driven by cooler air temperatures and winds. Modeling the physical mixing, temperature and oxygen regimes in tropical reservoirs 30 such as Kariba and Itezhzi-Tezhi could quantify the projected effects of climate warming and increased fertilizer loads on water quality in downstream river reaches.…”
Section: Dams and Hypoxiamentioning
confidence: 99%
“…However, all those conclusions cannot be directly applied to tropical case studies where the hydrological regime is different (Winton et al, 2019). Nevertheless, based on the studies mentioned above, it is necessary to go deeper into studies that directly relate water quality to hydrological and meteorological factors in hydropower systems in tropical latitudes (Calamita, 2020).…”
Section: Introductionmentioning
confidence: 99%